An Analysis of Undergraduate Students’ Ability and Their Difficulties in Identifying Simple, Compound, Complex, and Compound-Complex Sentences - Maulana, Surya; Markhamah, Yuli; Jailani, Ahmad (INOVISH JOURNAL, 2023)
This paper discusses the result of an analyzing the ability of undergraduate students about the difficulty of identifying simple sentence, compound sentence, complex sentence, and compound-complex sentence. A descriptive quantitative approach and a descriptive qualitative approach  are used in this study. Descriptive quantitative are used to see the student  score test in analyzing simple sentence, compound sentence, complex sentence, and compound-complex sentence. Descriptive qualitative are used to see the result of students interview in their difficulty of identifying simple sentence, compound sentence, complex sentence, and compound-complex sentence. This study shows that student average is 11.84 from 20 point, the median is 12 from 20 point, and the range is 6 (as a lower score) and 17 (as a highest score) from 20 point. Most of the students still have a difficulty in identifying the formation of simple sentence, compound sentence, complex sentence, and compound-complex sentence. Especially because they still don’t understand about connectors in the four types of sentences, such as subordinate connectors. Therefore students are required to practice writing in order to make it easier forming a simple sentence, compound sentence, complex sentence, and compound-complex sentence.